Gambaran Pemanfaatan Sarana dan Prasarana pada Kegiatan Life Skill Menjahit Seprai di PKBM Tenggang Raso Kota Padang - Siregar, Ikhsan; Sunarti, Vevi (Jurnal Family Education, 2023)
The background of this research is the high participation and interest in learning among the students in sewing bed sheets at PKBM Tenggang Raso in Padang City. It is suspected that there are supporting factors in the use of facilities and infrastructure in the activity of sewing sheets. The aims of this study were (1) to describe the use of the physical conditions of the practice room in bed linen sewing training; (2) describe the use of sewing equipment and supplies in bed sheets sewing training; (3) describe the use of the arrangement of sewing equipment and supplies in bed sheets sewing training; (4) describes the use of books to support sewing life skills in bed sheets sewing training. This type of research is quantitative description with a sample of 75% of the population, namely as many as 30 people. This study shows the results, namely (1) The use of the physical conditions of the practice room in bed linen sewing training is complete and adequate; (2) Adequate use of sewing equipment and supplies in bed sheets sewing training; (3) Utilization of the arrangement of sewing equipment and supplies in bed sheets sewing training is also sufficient; (4) describes the use of life skill sewing books for bed sheets sewing training that are available and adequate for use.